Evidence for the improvement of fatigue in fibromyalgia: A 4‐week left dorsolateral prefrontal cortex repetitive transcranial magnetic stimulation randomized‐controlled trial. (10th April 2018) - Fitzgibbon, B.M.; Hoy, K.E.; Knox, L.A.; Guymer, E.K.; Littlejohn, G.; Elliot, D.; Wambeek, L.E.; McQueen, S.; Elford, K.A.; Lee, S.J.; Enticott, P.G.; Fitzgerald, P.B.
Abstract: Background: Fibromyalgia is a complex chronic disorder with few effective treatments currently available. One promising treatment option is repetitive transcranial magnetic stimulation (rTMS), a non‐invasive brain stimulation technique that has shown promise in disorders effecting the central nervous system. Methods: We assessed the efficacy of a course of high‐frequency (10 Hz) left‐hemisphere dorsolateral prefrontal cortex (DLPFC) rTMS in 26 patients (14 active; 12 sham) with a diagnosis of fibromyalgia. Participants underwent a double‐blind stimulation protocol of daily (Monday–Friday) rTMS sessions over four consecutive weeks (total of 20 sessions; 75 × 4‐s 10 Hz trains at 120% resting motor threshold). Assessments were conducted at baseline, 4 weeks and at 1‐month follow‐up. Results: Using mixed‐model analysis we did not identify a group difference for our primary outcome measures. However, we found that patients in the active group compared to sham treatment group had significantly greater improvement in the Physical Fatigue ( p  =   0.045) and General Fatigue ( p  =   0.023) scales of the Multidimensional Fatigue Inventory‐20 at the 1 month follow‐up. In a responder analysis, we also found the active group was significantly more likely (2.84 times) to achieve a minimum 30% improvement in pain intensity ratings. ( p  =   0.024). Conclusions: High‐frequency rTMS applied daily for 4 weeks to the left DLPFC induces significant relief from fatigue and a greater chance of clinically meaningful improvement in pain intensity in patients with fibromyalgia. These results suggest DLPFC rTMS may be a relevant therapy for fibromyalgia. Significance: This study provides evidence that 4‐weeks of daily rTMS to the left DLPFC is able to improve fatigue in fibromyalgia. This novel finding provides impetus for the further investigation of the utility of TMS approaches for the relief of fatigue, an otherwise difficult‐to‐treat symptom, in fibromyalgia and related disorders.